On some Niphargus (Orniphargus) species (Crustacea, Gammaridea, fam. Niphargidae) from the Balkans (Contribution to the knowledge of the Amphipoda 278) - Karaman, Gordan S. (Biologia Serbica, 2016)
Several taxa of the subgenus Niphargus (Orniphargus) (Amphipoda: Gammaridea, fam. Niphargidae) from the western Balkan are investigated. The very briefly described species Niphargus (Orniphargus) pachytelson Sket, 1960 is redescribed from the type locality “Jama pri Luknji” Cave near Novo Mesto, and Podpeška Jama Cave in Slovenia, and its relationship regarding N. salonitanus S. Karaman, 1950 and some other similar taxa is discussed. Niphargus (Orniphargus) steueri subtypicus Sket, 1960 is redescribed from the type-locality cave “Jama pri Stolbah” near Črnomelj, Slovenia and its relationship to Niphargus jalzici G. Karaman, 1989 and some other taxa is discussed. Niphargus (Orniphargus) steueri kolombatovici S. Karaman, 1950 is cited from new caves in Bosnia and Herzegovina. A key to the subspecies Niphargus (Orniphargus) steueri Schellenberg, 1935 is presented. Niphargus (Orniphargus) arbiter G. Karaman 1984 is discovered in new localities in Croatia and Bosnia and Herzegovina.